2013
DOI: 10.5172/conu.2013.45.1.56
|View full text |Cite
|
Sign up to set email alerts
|

Individual-level outcomes from a national clinical leadership development programme

Abstract: A national clinical leadership development programme was instituted for Irish nurses and midwives in 2010. Incorporating a development framework and leadership pathway and a range of bespoke interventions for leadership development, including workshops, action-learning sets, mentoring and coaching, the programme was introduced at seven pilot sites in the second half of 2011. The programme pilot was evaluated with reference to structure, process and outcomes elements, including individual-level programme outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…All interventions for clinical leadership development included in this review were implemented in High-Income Countries (HIC). Thirteen papers reported on studies conducted in the United Kingdom (UK) (England, Ireland and Scotland) [ 25 – 37 ] while six reported studies in Australia [ 23 , 38 42 ] and three in the United States of America (USA) [ 24 , 43 , 44 ]. One study was conducted in Belgium [ 45 ] and one in Switzerland [ 46 ] (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All interventions for clinical leadership development included in this review were implemented in High-Income Countries (HIC). Thirteen papers reported on studies conducted in the United Kingdom (UK) (England, Ireland and Scotland) [ 25 – 37 ] while six reported studies in Australia [ 23 , 38 42 ] and three in the United States of America (USA) [ 24 , 43 , 44 ]. One study was conducted in Belgium [ 45 ] and one in Switzerland [ 46 ] (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The emphasis of most interventions was on developing clinical skills. Some interventions were designed to develop leadership competencies, to promote succession planning, to enhance the contribution of frontline healthcare providers to patient experiences, and to ensure quality and safe health services [ 23 31 , 36 , 37 , 39 42 , 44 46 ] (Table 2 ). Other interventions focused on preparing nursing students, medical students, and novice frontline healthcare providers for future leadership roles and for ensuring quality care and patient safety [ 33 , 35 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…In general, studies in nursing have investigated either leadership professional competence or management professional competence (Casida and Parker 2011;Cummings et al, 2010;Hutchinson and Purcell, 2010;Jasper and Crossan, 2012;McCallin and Frankson, 2010;Supamanee et al, 2011;Thomson and Hall, 2011;Westphal, 2012;Wood, 2011), and have looked at inter alia, human resource management, change and performance management, and leadership behaviours, standards and requirements (Azaare and Gross, 2011;Fealy et al, 2011;Macphee and Suryaprakash, 2012;Patton et al, 2013;Supamanee et al, 2011). Furthermore, several studies have described the role of the nurse manager as lists of competencies, talents and traits which can be found in successful nurse managers (Casida and Parker, 2011;Cummings et al, 2010;Hutchinson and Purcell, 2010;Jasper and Crossan, 2012;McCallin and Frankson, 2010;Supamanee et al, 2011;Thomson and Hall, 2011;Westphal, 2012;Wood, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Nurses are responsible for a variety of management and care actions in the hospital environment. A study conducted with nurses of a university hospital in Finland, using the instrument Nurse Competence Scale (NCS), found that, among the 458 nurses, the highest scoring responses were those related to the role of care (68.4) and situation management (67.5) (12) . In a program for the development of clinical leadership conducted in Ireland, participants chose the following as main necessary competences for the function: quality and safety, clinical excellence, self-conscience, decision-making and communication (13) .…”
Section: Discussionmentioning
confidence: 99%